2011
DOI: 10.1002/chem.201100684
|View full text |Cite
|
Sign up to set email alerts
|

Telomerisation of Buta‐1,3‐diene and Methanol: Superiority of Chromanyl‐Type Phosphines in the Dow Process for the Industrial Production of 1‐MOD

Abstract: Butadiene and methanol were telomerised in the presence of palladium catalysts with ligands containing 8-diphenylphosphinochromane-like substituents at phosphorus. MonoXantphos and monoSPANphos afforded the most active, stable and selective catalysts known to date under commercially relevant production conditions for 1-methoxyocta-2,7-diene, the precursor to oct-1-ene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…By variation of the base concentration, a strong influence on the reaction rate was observed resembling a first-order dependency in the base concentration. This strong influence was already discussed in the literature [13]. Furthermore, the variation of the base strength showed that the Pd-IMes catalyst seems to be only efficiently activated by a strong base such as KOMe.…”
Section: Imes Ligandsupporting
confidence: 59%
See 1 more Smart Citation
“…By variation of the base concentration, a strong influence on the reaction rate was observed resembling a first-order dependency in the base concentration. This strong influence was already discussed in the literature [13]. Furthermore, the variation of the base strength showed that the Pd-IMes catalyst seems to be only efficiently activated by a strong base such as KOMe.…”
Section: Imes Ligandsupporting
confidence: 59%
“…Compared to the traditional phosphine-modified systems, higher chemo-and regioselectivity and significantly higher activity have been reported. To the best of our knowledge, all previously reported telomerization catalysts have been applied to either pure 1,3-butadiene feedstock or a technical diluted feed [1,[10][11][12][13][14][15][16]. Here we present for the first time a comparative study of both phosphine and NHC-modified palladium catalysts with pure and mixed butadiene feed.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H, 13 C, 11 B, 31 P, and 19 FNMR spectra were recorded on Bruker AvanceI II HD nanobay 400 MHz or Bruker AvanceI II 500 MHz spectrometer at ambient temperature and referenced internally to residual protio-solvent ( 1 H) or solvent ( 13 C) resonances and are reported relative to tetramethylsilane (d = 0ppm), 31 Pr esonances are referenced externally to H 3 PO 4 (85 %), 19 Fc hemical shifts to CF 3 COOH, and 11 Bc hemical shifts to BF 3 ·Et 2 O. Solvents were degassed by sparging with argon and dried by passing through ac olumn of the appropriate drying agent and stored over potassium or 4 sieves.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent work demonstrated that mono‐ as well as diphosphines based on a dibenzodioxocin backbone ( L7 ) are capable of comparable activities under the same conditions . Furthermore, this group was able to demonstrate that chromanyl backbones lead to very effective ligands, for example ( L8 ) …”
Section: Catalystsmentioning
confidence: 99%